Effects of exposure to global marketing activities on consumption behavior among university students in the Klang Valley, Malaysia - Akhoundi, Maryam (2017)
Among factors that influence consumer behavior, the most purposive is the effect of exposure to global marketing activities. To take advantage of standardization, global companies perform marketing campaigns and strategies which are viewed as serious threats to local economy and culture. Therefore, the primary objective of this study was to ascertain the effect of exposure to global marketing activities on consumption behaviors (of global foods and drinks, personal care items, global clothing and accessories, household appliances, electronics, communications and luxury goods). Despite a huge study on this topic, lacking of mediating role of consumer individual values and absolute absence of moderating effect of domestic global brand attitude and consumer ethnocentric tendency simultaneously were found in literature. Hence, the theoretical framework of this study was established based on the model of dynamic influence of acculturation to global consumer culture and ethnic identification on consumption behavior, the theory of homogeneity and heterogeneity, dynamic, multilevel model of culture and theory of basic values. A survey of 479 respondents using self-administrated questionnaires was conducted across university students from three main ethnics in Malaysia. Using descriptive analysis, CFA, one-way ANOVA, Structural Equation Modeling analysis with bootstrap and multiple regression analysis, the study indicated following results based on a relatively good fit of the model to the data. Out of all consumption behaviors, exposure to global marketing activities significantly predicted global foods and drinks, global clothing and accessories, household appliances and communications consumption. A moderate level of exposure to global marketing activities was observed among respondents. Regarding consumption behavior, the highest level was identified in consumption of communications followed by personal care items, household appliances, global clothing and accessories, global foods and drinks, electronics, and the last and least, luxury goods. The study supported the possibility of both homogeneity and heterogeneity in consumption behavior by contribution of exposure to global marketing activities but depending on product category. Domestic global brand attitude and consumer ethnocentric tendency were recognized as moderators on the relationship between predictor variable and consumption behaviors of global foods and drinks and household appliances. Furthermore, all higher levels of consumer individual values mediate the relationship between predictive variable and household appliances and communications consumption. While for consumption behaviors of global foods and drinks, and global clothing and accessories, no mediating effect was observed. The findings suggest that both mediating and moderating effects vary from behavior to behavior. The main contribution of this study is to expand the knowledge of consumer behavior by incorporating the psychological constructs of consumer individual values, domestic global brand attitude and consumer ethnocentric tendency. The study provided some implications and recommendations on consumption behavior of the respondents for interested entities. The necessity for further study on consumption behavior was also emphasized.